Exploring mental health literacy and barriers to seeking counselling among university students in Lebanon: a cross-sectional study - Samar Younes; Dana Ayoub; Racha Baalbaki; Andre Slim; Leila Yassine; Natalie Abdelghani; Mohamad Rahal; Nisreen Mourad (BMJ Open, 2025)
Objectives This study aims to assess the level of mental health literacy (MHL) and identify its associated factors among undergraduate university students in Lebanon. A secondary objective is to evaluate the Global Barriers to Counselling scores, their associated factors, and to examine their relationship with MHL.Design Cross-sectional study using an online self-administered questionnaire.Setting University-level educational settings in Lebanon, including students from both public and private institutions across multiple regions.Participants This study enrolled undergraduate students of all academic disciplines using a convenience sampling technique. Inclusion criteria included being 18 years and above, currently enrolled at university, able to comprehend the English language and consenting to participate.Primary and secondary outcome measures Primary outcomes: MHL scores, using the Mental Health Literacy Scale (MHLS); and Global Barriers to Counselling score, using the Revised Fit, Stigma and Value Scale (RFSV). Secondary analysis examined factors associated with MHLS score and Global Barriers to Counselling scores using multivariable linear regression.Results A total of 572 participants (65.0% female; mean age 21.1±3.7 years) were included. Most were Lebanese (87.4%). The median MHLS score was 86 (IQR 77–95), indicating generally good MHL. Factors associated with lower MHLS were male gender (β=−4.17, 95% CI −7.18 to −1.16, p=0.007) and being of non-Lebanese nationality (β=−6.26, 95% CI −11.06 to −1.46, p=0.011). Presence of a previous mental health diagnosis was associated with a higher MHLS score (β=5.32, 95% CI 1.43 to 9.22, p=0.008). The Global Barriers to Counselling score had a median of 28.7 (IQR 23.21–36.21). Male gender was significantly associated with a higher barrier score (β=3.44, 95% CI 4.85 to 5.04, p<0.001). Factors associated with lower barrier score were attending a mental health seminar in the past (β=−2.00, 95% CI −3.91 to −0.09, p=0.04), and having a higher MHLS score (β=−0.14, 95% CI −0.21 to −0.07).Conclusion This study highlights good overall MHL among undergraduate university students in Lebanon, with variations based on gender, nationality and prior mental health exposure. Higher mental health literacy was associated with fewer perceived barriers to seeking counselling. These findings emphasise the need for tailored mental health initiatives in Lebanese universities that promote literacy, reduce stigma and enhance help-seeking behaviour across diverse student populations.